Landscape Design with Edibles - Gail Hansen (EDIS)
Although design basics for edible ornamental landscapes are essentially the same as strictly ornamental landscapes, a few details ensure the success of the edible landscape. Gardens with plants that change considerably with the seasons rely more on an organized yet interesting layout, appealing support structures, functional pathways, and colorful containers and planters to provide interest and beauty when the plants are not taking center stage. There are twelve important ideas to consider when creating a successful edible ornamental garden. This 4-page fact sheet was written by Gail Hansen, and published by the UF Department of Environmental Horticulture, May 2013.